Metode dan Karakteristik Nabi Muhammad SAW Dalam Pendidikan - Wahyu Ningsih; Ani Fitriyani; Robithoh Izzati Hanani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research is library research with data collection methods using documentation methods. Meanwhile, data analysis uses descriptive analysis methods. In this case the author as a researcher tries to describe by regularly exemplifying the teaching methods and techniques of the Prophet Muhammad SAW. From the research results it can be concluded that the Prophet Muhammad was one of the world's educational figures. He has practiced many teaching methods and techniques with his friends. For example, the methods of Story Telling, Self Reflection, Learning and Motivating, Body Language, Asking, Questions and so on. We as educators must be able to emulate what he has practiced